2019
DOI: 10.1111/vsu.13270
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental principles of rehabilitation and musculoskeletal tissue healing

Abstract: ObjectiveTo review fundamental principles of tissue healing and physical rehabilitation as they apply to dogs recovering from cranial cruciate ligament (CCL) surgery.Study designInvited Review.Sample populationNone.MethodsA multidisciplinary group of specialists in small animal surgery, rehabilitation/sports medicine, and human physical and occupational therapy reviewed the currently available evidence for rehabilitation post‐CCL surgery. Because current evidence is limited, this group proposes guidelines for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 48 publications
2
35
0
2
Order By: Relevance
“…Marcellin-Little and collaborators [34] reported that in sports dogs, muscle recovery takes more than 6 weeks. A recent publication has also investigated the time required for muscle healing on the basis of injury grading; the authors reported grade 2 lesions had a very wide range from 3 weeks to 3-6 months [35].…”
Section: Discussionmentioning
confidence: 99%
“…Marcellin-Little and collaborators [34] reported that in sports dogs, muscle recovery takes more than 6 weeks. A recent publication has also investigated the time required for muscle healing on the basis of injury grading; the authors reported grade 2 lesions had a very wide range from 3 weeks to 3-6 months [35].…”
Section: Discussionmentioning
confidence: 99%
“…In the histological evaluation, we observed treated wounds with both Carbopol and murumuru butter Jucá-based formulations to have a better epithelization process. Wounds treated with the herbal formulation had connective tissue with a large number of active fibroblasts, better organized collagen fibers, and few blood vessels, in contrast to the control group, where a moderate amount of fibroblasts, disorganized collagen fibers, and newformed vessels were observed, demonstrating the need for additional time to complete the epithelization process (26). Previous reports also demonstrated that the healing process was facilitated by phytotherapeutics with this plant (7,25).…”
Section: Wound Healing In Dogsmentioning
confidence: 92%
“…Those results support our choice for the methodological approach used to repeat all treatments in each animal. Dermal healing varies according to immune and nutritional status but genetic factors can also be associated (26). Furthermore, our study standardized the health and nutrition of all animals, and we used dogs from different genetic backgrounds.…”
Section: Wound Healing In Dogsmentioning
confidence: 99%
“…When combined, the comparison of gait and incline was analyzed in the present report, and walking uphill did not show significant differences, with trotting flat and trotting downhill, in mean and maximum sEMG activities. In canine rehabilitation, choosing between one of these exercises would depend on the stage of rehabilitation and patient's conditions [1].…”
Section: Longissimus Dorsi Musclementioning
confidence: 99%
“…In the past decade, knowledge of canine physical therapy has experienced growing advances, being today very helpful and established professional services complementing the multidisciplinary veterinary team. Canine rehabilitation requires multimodal treatments applied to each patient on the basis of its specific needs [1]. To be efficient, physical therapists and veterinary surgeons need a thorough and scientifically-based understanding of the kinematics and muscle function in the therapeutic exercises prescribed.…”
Section: Introductionmentioning
confidence: 99%